The ASPECTUL TEORETIC VIZÂND INCLUDEREA PIEŢEI TENEBRE ÎN CIRCUITUL ECONOMIC LEGAL - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2007)
The article proposes different means to solve the issue of transition of the underground sector of the economy to legal and transparent market relations. The author stresses that the problem is conditioned by the fact that the fraudulent economy activity in the actual society constitutes a “true” component of its existence and cannot be repressed, regulated or destroyed by the state through repressive methods. The more the state regulation process of the economic activity grows, the more economic frauds phenomena extend. A special emphasis is put on economic reforms at macroeconomic level. The article shows the ways of approach the liberalization of the underground market for the purpose to remove the fundamental causes of these phenomena, especially providing freedom and liberalization to all kinds of economic activity.